Role of Tonic Inhibition in Associative Reward Conditioning in Lymnaea - Marra, Vincenzo; Kemenes, Ildikó; Vavoulis, Dimitris; Feng, Jianfeng; O'Shea, Michael; Benjamin, Paul R. (Frontiers in Behavioral Neuroscience, 2010)
Changes in the strength of excitatory synaptic connections are known to underlie associative memory formation in the molluscan nervous system but less is known about the role of synaptic inhibition. Tonic or maintained synaptic inhibition has an important function in controlling the Lymnaea feeding system and is known to suppress feeding in the absence of food or in satiated animals. Tonic inhibition to the feeding network is provided by the N3t interneuron that has inhibitory monosynaptic connection with the central pattern generator interneuron, the N1M. Here we asked whether a reduction in the level of tonic inhibition provided by the N3t cell could play a role in reward conditioning? Semi-intact preparations made from hungry snails were conditioned using a previously-developed one-trail chemical conditioning paradigm. We recorded electrical activity in a feeding motoneuron, the B3, at various time-points after conditioning. This allowed us to measure the frequency of spike activity in the N3t interneuron and monitor fictive feeding patterns that generate the rhythmic movements involved in food ingestion. We show that there is a reduction in N3t spiking at 1, 2, 3 and 4 hours after conditioning but not at 10 minutes and 30 minutes and the reduction in N3t firing inversely correlates with an increase in the conditioned fictive feeding response. Computer simulation of N3t-N1M interactions suggests that changes in N3t firing are sufficient to explain the increase in the fictive feeding activity produced by conditioning. A network model is presented that summarizes evidence suggesting that reward conditioning in Lymnaea is due to the combined effects of reduced tonic inhibition and enhanced excitatory synaptic connections between the CS pathway and feeding command neurons.